2019
DOI: 10.1007/s00701-019-03885-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different hydrocortisone treatment strategies in transsphenoidal pituitary surgery

Abstract: Background Hydrocortisone treatment in transsphenoidal pituitary surgery has been debated. Although several publications advocate restrictive treatment, centers around the world administer stress doses of hydrocortisone in patients with presumed intact cortisol production. Our aim with this analysis was to compare postoperative hypocortisolism in patients who received three different protocols of hydrocortisone therapy during and after surgery. Method This was a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…An interesting finding in our study is the fact that a fairly large group of patients increased their need for postoperative hormonal substitution after surgery. The majority of these patients were treated with postoperative hydrocortisone as additional hormonal substitution and we know from a previous study that hydrocortisone treatment is more commonly used in our institution compared to international standards [10]. This fact may very well influence the true need for postoperative hormonal substitution, and should perhaps be analyzed in detail separately.…”
Section: Discussionmentioning
confidence: 97%
“…An interesting finding in our study is the fact that a fairly large group of patients increased their need for postoperative hormonal substitution after surgery. The majority of these patients were treated with postoperative hydrocortisone as additional hormonal substitution and we know from a previous study that hydrocortisone treatment is more commonly used in our institution compared to international standards [10]. This fact may very well influence the true need for postoperative hormonal substitution, and should perhaps be analyzed in detail separately.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, they concluded that there is no necessity to receive routine cortisol replacement for patients with normal morning serum cortisol levels. Fridman-Bengtsson et al 32 evaluated different hydrocortisone treatment strategies in transsphenoidal pituitary surgery. The authors compared three groups: high dose, intermediate dose and low dose hydrocortisone substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they concluded that there is no necessity to receive routine cortisol replacement for patients with normal morning serum cortisol levels. Fridman-Bengtsson et al evaluated different hydrocortisone treatment strategies in transsphenoidal pituitary surgery [31].…”
Section: Discussionmentioning
confidence: 99%